Analisa Faktor - Faktor yang Mempengaruhi Nilai Perusahaan Sektor Konsumsi - Barita, Gilbert Austin; Ekadjaja, Agustin (Jurnal Paradigma Akuntansi, 2025)
In an empirical study conducted from 2018 to 2021, the purpose of this study is to observe and evaluate the impact of firm size, profitability, liquidity, and leverage on firm value in manufacturing companies in the consumption sector listed on the Indonesia Stock Exchange (IDX). Purposive sampling was used to select 16 manufacturing companies from the consumption sector for this study, which used 64 data points from the previous four years. Secondary data in the form of financial statements for a specific time period that ended on January 1 are used. The statistical software IBM SPSS 22 is used to analyze the data in this study. According to the study's findings, firm size and leverage have a significant negative impact on firm value, liquidity has a negligible positive impact on firm value, and profitability has a significant positive impact on firm value. to the company's worth.